An experimental evaluation of the methodology proposed for the monitoring and certification of CO2 emissions from heavy-duty vehicles in Europe. (1st May 2016) - Fontaras, Georgios; Grigoratos, Theodoros; Savvidis, Dimitrios; Anagnostopoulos, Konstantinos; Luz, Raphael; Rexeis, Martin; Hausberger, Stefan
Abstract: The European Commission is preparing a new regulatory initiative for monitoring CO2 emissions and fuel consumption of Heavy-Duty Vehicles in Europe. The new methodology is based on a combination of component testing and computer simulation of the vehicles' fuel consumption. A study was launched aiming to demonstrate that the approach is accurate and representative of the actual performance of vehicles. Experiments were conducted on two trucks, a 40 t Euro VI long haul truck and an 18 t Euro V rigid truck. Measurements were performed both on the chassis dyno and on the road. Simulation software was used for simulating the tests. Its ability to capture vehicle performance and fuel consumption was assessed against the measured data. Simulation results closely matched those of the dyno tests with the final simulated fuel consumption deviating by about ±2–4% compared to the measured value. Over the tests performed on the road, the final fuel consumption laid within a ±3.5% from the measurement. Given the variability of the actual measurement (σ ≥ 2%), it is concluded that a future official vehicle certification scheme can be based on this approach and achieve both high representativeness, compared to the vehicle's actual performance and high vehicle-to-vehicle, accuracy. Highlights: Heavy duty vehicle sector is important, actions are proposed for curbing its CO2 emissions worldwide. A simulation based certification for CO2 emissions from heavy duty vehicles is developed in Europe. The simulation approach proposed is intended for certification and monitoring purposes. Simulation can accurately capture differences in fuel consumption and CO2 between different vehicles. The proposed certification method appears representative of actual real world performance.